2009
DOI: 10.1093/cvr/cvp335
|View full text |Cite
|
Sign up to set email alerts
|

Long-term improvement in mdx cardiomyopathy after therapy with peptide-conjugated morpholino oligomers†

Abstract: These results demonstrate for the first time that PPMO-mediated exon skipping therapy early in the course of DMD may effectively prevent or slow down associated cardiac hypertrophy and diastolic dysfunction with significant long-term impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 44 publications
5
63
1
Order By: Relevance
“…This dysfunction usually precedes the onset of systolic heart failure and dilated cardiomyopathy (Markham et al, 2006). Mdx mice show these same echocardiographic abnormalities (Jearawiriyapaisarn et al, 2010;Townsend et al, 2007).…”
Section: Pde-5 Inhibitors Reverse Cardiac Dysfunction In Duchenne Musmentioning
confidence: 93%
“…This dysfunction usually precedes the onset of systolic heart failure and dilated cardiomyopathy (Markham et al, 2006). Mdx mice show these same echocardiographic abnormalities (Jearawiriyapaisarn et al, 2010;Townsend et al, 2007).…”
Section: Pde-5 Inhibitors Reverse Cardiac Dysfunction In Duchenne Musmentioning
confidence: 93%
“…Many approaches have been tested. Cell penetrating peptides (Jearawiriyapaisarn et al, 2008;Jearawiriyapaisarn et al, 2010; www.intechopen.com al., 2008; Yin et al, 2008), muscle targeting peptides connected to cell penetrating peptides (Yin et al, 2009) and guanidine analogs (Hu et al, 2010;Wu et al, 2009) showed the most promising results in the mdx mouse and in the hDMD mouse model (Wu et al, 2011a). Notably, pPMOs (containing arginine-rich peptides covalently bound to the morpholino AONs) have shown great potential in the mdx mouse, inducing high levels of exon skipping in skeletal muscles and heart and high levels of dystrophin rescue.…”
Section: Aon Chemistry Developmentmentioning
confidence: 99%
“…4 ECU, extensor carpi ulnaris; EDL, extensor digitorum longus; GC, gastrocnemius; i.a., intra arterial injection; i.c., intra cardiac injection; i.m., intra muscular injection; i.v., intravenous injection; i.p., intra penetrial injection; QUAD, quadriceps; s.c., Subcutaneous injection; TA, tibilias anterior. 5 IH, immunohistochemistry; WB, Western blot; wt, wild type. 2 (where R is arginine, X is 6-aminohexanoic acid, B, β-alanine); F127, block co-polymer transfection; Lipofectin, cationic lipids; MSP (Muscle specific peptide), ASSLNIA; PEG, Polyethylene glycol; Pip1, (RXR) 3 -IKILFQNRRMKWKKC; Pip2a, (R-X-R) 3 -IdKILFQNdRRMKWHKBC; Pip2b, (RXR) 3 -IHILFQNdRRMKWHKBC; PLGA, poly(lactic-co-glycolic acid); PMMA, poly(methyl methacrylate); PEI, polyethylenimine; SAINT, cationic pyridinium transfection reagent; Tat, YGRKKRRQRRRP.…”
Section: Animal Modelsmentioning
confidence: 99%
“…4 ECU, extensor carpi ulnaris; EDL, extensor digitorum longus; GC, gastrocnemius; i.a., intra arterial injection; i.c., intra cardiac injection; i.m., intra muscular injection; i.v., intravenous injection; i.p., intra penetrial injection; QUAD, quadriceps; s.c., Subcutaneous injection; TA, tibilias anterior. 5 IH, immunohistochemistry; WB, Western blot; wt, wild type. and they have to be repeatedly administered for the lifetime of the patient or until another treatment option becomes available.…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation